Border Optics : Surveillance Cultures on the US-Mexico Frontier - Fojas, Camilla, 1971- (Book collections on Project MUSE., 2021)
"This book argues that the U.S.-Mexico border is both a laboratory and an archive that indexes an optical regime and a way of seeing that combines fascination with the region with the visual codes of surveillance and survey"--